2017
DOI: 10.1097/njh.0000000000000308
|View full text |Cite
|
Sign up to set email alerts
|

Making Sense of Moral Distress Within Cultural Complexity

Abstract: The aim of this study was to explore nurses’ experiences working on a chronic ventilator-dependent unit with a predominance of elderly Orthodox Jewish patients at the end of life. Little is known about how cultural complexity creates differences between nurses’ and family’s expectations for patient care at the end of life. A qualitative study of 27 nurses was conducted using focus groups. Early interviews led to the expansion of the original question to include exploring nurses’ moral distress. Content analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(29 citation statements)
references
References 9 publications
2
27
0
Order By: Relevance
“…Similar to Bressler, Hanna, and Smith, [9] the nurses in this study experienced internal conflict related to caring for patients with contrary beliefs and practices. As noted in the theme moral code, these differences challenged the nurse's values adding to their internal conflict and their moral obligation to care.…”
Section: Discussionmentioning
confidence: 84%
See 4 more Smart Citations
“…Similar to Bressler, Hanna, and Smith, [9] the nurses in this study experienced internal conflict related to caring for patients with contrary beliefs and practices. As noted in the theme moral code, these differences challenged the nurse's values adding to their internal conflict and their moral obligation to care.…”
Section: Discussionmentioning
confidence: 84%
“…Yap [10] makes a case for personal beliefs as influential in moral decision making and identified the need for an ethical framework in social-scientific education for students early on in their careers. Bressler, Hanna, and Smith's [9] study showed nurses did experience internal conflict when providing care that was contrary to their values; nurses in their study asked for more education on cultural and religious issues to improve their ethical practice.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations